A systematic review on the influence of fear of falling on quality of life in older people: is there a role for falls? - Schöne, Daniel; Heller, Claudia; Aung, Yan N.; Sieber, Cornel; Kemmler, Wolfgang; Freiberger, Ellen (Clinical Interventions in Aging, 2019)
Maintaining or improving quality of life (QoL) is a key outcome of clinical interventions in older people. Fear of falling (FoF) is associated with activity restriction as well as with poorer physical and cognitive functions and may be an important contributor to a diminished QoL. The objectives of this systematic review were to determine i) the effect of FoF on QoL in older people, ii) whether the association between these two constructs depends on the use of specific conceptualizations and measurement instruments, and iii) the role of fall events as mediating factor in this relationship. Four electronic databases (PubMed, EMBASE, CINAHL, and Cochrane Library) were searched from their inceptions to February 2018. Thirty mostly cross-sectional studies in nearly 30.000 people (weighted mean age 75.6 years (SD =6.1); 73% women) were included. FoF was associated with QoL in most studies, and this association appeared to be independent of the conceptualization of FoF. Moreover, this relationship was independent of falls people experienced which seemed to have a lower impact. FoF should be considered not only as by-product of falls and targeted interventions in parts different from those to reduce falls are likely required. Studies are needed showing that reducing FoF will lead to increased QoL.
CRIS-Team WoS Importer:2019-05-09